The work process for the promotion of students with special needs integrated in the kindergartens of regular education: the case of Israel - Bar, Nava (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The Special Education Law in Israel was legislated on July 12, 1988. The law determined precedence and advance preference for the placement of special needs students in the regular educational system over the special education system. In the spirit of the law, methodical and painstaking processes that arrange the work with special needs students in the educational system were determined. This article presents two work processes implemented in parallel in the regular kindergartens. The first work process is with students who have functional difficulties, before their definition and as prevention of their definition as students with special needs. The second process is the work process with the special needs students who are integrated in the regular kindergartens, intended to prevent their referral to frameworks of special education. These processes reflect the development that occurred in the importance ascribed in the educational system in Israel to careful and adjusted work with students who have difficulties and special needs and are integrated in the kindergartens of regular education. Alongside the described development, the article presents the challenges and the questions that the implementation of the processes poses.